The value of using rapid rural appraisal techniques to generate and record indigenous knowledge : the case of indigenous vegetables in Uganda - Hart, Tim George Balne (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA)--University of Stellenbosch, 2004.